Post-truth schooling and marketized education: Explaining the decline in Sweden's school quality - Magnus Henrekson; Johan Wennström (Research Institute of Industrial Economics (IFN), 2018)
The Swedish school system suffers from profound problems with teacher recruitment and retention, knowledge decline, and grade inflation. Absenteeism is high, and psychiatric disorders have risen sharply among Swedish pupils in the last ten years. In this pioneering analysis of the consequences of combining institutionalized social constructivism with extensive marketization of education, we suggest that these problems regarding school quality are to no small extent a result of the Swedish school system's unlikely combination of a postmodern view of truth and knowledge, the ensuing pedagogy of child-centered discovery, and market principles. Our study adds to the findings from previous attempts to study the effects of social-constructivist pedagogy in nonmarket contexts and yields the implication that caution is necessary for countries, notably the U.S., that have a tradition of social-constructivist practices in their education systems and are considering implementing or expanding market-based school reforms.
Keywords: H42; H44; H75; I22; I28; L88; 330; For-profit schools; Marketized education; School choice; Social constructivism; Voucher system